Corrosion method for displaying original austenite grain boundary of martensitic steel

By using a corrosion method of a mixed solution of hydrofluoric acid and hydrogen peroxide and an aqueous solution containing potassium permanganate and concentrated sulfuric acid, the original austenite grain boundary of martensitic steel is shown, solving the problem of complex and low applicability of the grain boundary in the prior art, and achieving a simple and efficient grain boundary display effect.

CN120232704APending Publication Date: 2025-07-01TAIYUAN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510719641.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-30
Publication Date
2025-07-01

AI Technical Summary

Technical Problem

The prior art is difficult to effectively display the original austenite grain boundaries of martensite steel. It is complex in operation, time-consuming, and has a narrow range of application. It is limited by the material state and its applicability is not wide enough.

Method used

A mixed solution of hydrofluoric acid and hydrogen peroxide is used as a corrosion agent. After wiping the sample with degreased cotton in the corrosion solution, the sample was subjected to thermal corrosion, and further corrosion was performed using an aqueous solution containing potassium permanganate and concentrated sulfuric acid. Finally, the aqueous solution of oxalic acid was used to clean, showing the original austenite grain boundary of martensite steel.

Benefits of technology

It realizes a clear display of the original austenite grain boundary of martensite steel, which is easy to operate, high efficiency, low risk, and does not require electrochemical corrosion. It is suitable for martensite steel with medium and low carbon and Cr content ≤15wt%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120232704A_ABST
    Figure CN120232704A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of steel and iron material performance detection, in particular to a corrosion method for displaying the original austenite grain boundary of martensitic steel, a corrosion solution does not contain picric acid, a nitric acid alcohol solution and an aqua regia solution, the danger is low, raw materials are easy to obtain, the corrosion process is easy to operate, and the efficiency is high. The original austenite grain boundary of the martensitic steel can be clearly displayed without using electrochemical corrosion complex equipment; a mixed solution of hydrofluoric acid and hydrogen peroxide is selected as a corrosive agent for the austenite grain boundary of the martensitic steel, the corrosivity of the corrosive agent is just matched with the corrosion resistance of the grain boundary of the martensitic steel with medium and low carbon and the Cr content smaller than or equal to 15 wt%, the corrosive agent has sensitivity to the grain boundary, the grain boundary can be clearly displayed, the corrosive agent is not sensitive to an intragranular martensitic structure, and the good inhibition effect is achieved; therefore, a perfect austenite grain boundary display effect is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of performance testing of steel materials, and particularly to a corrosion method for revealing the original austenite grain boundaries of martensitic steel. Background Art

[0002] Cr5 steel is a high-quality steel, with excellent high-temperature strength and toughness, good wear resistance, fatigue resistance, corrosion resistance, and high-temperature hardness. It is mainly used for manufacturing hot working dies and is widely used in fields such as automobiles, bearings, and household appliances. Cr15 steel is a high-chromium tool steel with a chromium content of about 15%, which endows it with excellent wear resistance, good oxidation resistance, corrosion resistance, and high hardness. It is widely used in manufacturing components such as balls, rollers, and raceways in rolling bearings. In the aerospace environment, the oxidation resistance of Cr15 steel also makes it suitable for use. In the petrochemical field, it is used to manufacture key components of compressors and pumps. Due to its excellent performance in many application fields, its performance requirements are relatively strict. The original austenite grains and their uniformity directly affect various properties of the steel, such as performance indicators such as the strength, toughness, corrosion resistance, and fatigue resistance of the steel. Coarse austenite grains often lead to coarse structures obtained after the material is cooled, greatly reducing the comprehensive mechanical properties of the material. Therefore, the grain boundary display technology is an essential task in the production and research process of steel. And heat-resistant steels have strict requirements for grain size. Therefore, the display technology of the original austenite grain boundaries of heat-resistant steels is particularly important, and it has important significance for judging the microstructure evolution, properties, heat treatment processes, etc. of the material.

[0003] For Cr5 steel, when corroding grains by conventional corrosion methods, it is easy to appear martensite, pearlite, bainite and other microstructures. The corroded grain boundaries are easily covered by the intragranular microstructures, resulting in difficulty in revealing the grain boundaries. Currently, the commonly used corrosion methods are as follows: (1) Chemical etching method using a saturated picric acid aqueous solution containing sodium dodecylbenzenesulfonate as the etchant. This method has certain effects on carbon steel and quenched and tempered steel with uniform grain structure and low alloy element content, but limited by the material state, its applicability is not wide enough. (2) Using concentrated nitric acid and concentrated hydrochloric acid as the etchant. When using this etchant, the grain boundaries are revealed while the microstructures are also revealed. The color of the microstructures is dark gray or brownish black, which is easy to cover the contour of the grain boundaries; the morphology of the microstructures is obvious lath-shaped or needle-shaped, and the straight laths are easily confused with the polygonal grain boundaries. Sometimes the grain boundaries are incompletely revealed or difficult to reveal; (3) If using an etchant of hydrofluoric acid plus nitric acid and water to corrode, the martensite microstructure and grain boundaries are corroded simultaneously, making it difficult to count the grain size. Moreover, hydrofluoric acid is a highly corrosive acid, which is very harmful to the human body, and it is easy to cause danger during the preparation process in the laboratory. In the prior art, the following methods are generally also used to achieve grain boundary revelation: (1) Using heat treatment methods to make precipitates accumulate near the grain boundaries to reveal the grain boundaries, but this method requires heat treatment of the specimens, which is relatively troublesome and time-consuming; (2) Using electrolytic etching method, gently polishing the corroded specimens to reveal the grain boundaries, but the electrolytic etching method has high requirements for equipment; (3) Using the method of heating the etchant, corroding the specimens for 2 hours under the boiling condition of the etchant. The corrosion time is long. Although these corrosion methods can reveal the original austenite grain boundaries, they have complex operations, long time consumption, high requirements for operators, produce harmful gases that are harmful to operators, and have a narrow scope of application, limited by the material state, and insufficient applicability, which is not conducive to large-scale industrial applications. Summary of the Invention

[0004] In view of the technical problems existing in the prior art, the present invention provides a corrosion method for revealing the original austenite grain boundaries of martensitic steel.

[0005] According to one aspect of the present invention, the present invention provides the following technical solution:

[0006] A corrosion method for revealing the original austenite grain boundaries of martensitic steel, comprising the following steps:

[0007] S1. Prepare a martensitic steel metallographic specimen;

[0008] S2. Dip absorbent cotton in etching solution A, wipe the polished surface of the specimen forcefully until a silver-gray foggy surface appears, then immerse the polished surface of the specimen upward in etching solution B for thermal etching. After thermal etching, take out the specimen and rinse the residual etching solution on the surface of the specimen;

[0009] S3. Immerse the polished surface of the specimen to be tested after etching in the cleaning solution, then rinse and dry it to reveal the original austenite grain boundaries of the martensitic steel.

[0010] As a preferred embodiment of the etching method for revealing the original austenite grain boundaries of martensitic steel according to the present invention, wherein: in step S2, the etching solution A is a mixed solution of hydrofluoric acid and hydrogen peroxide with a volume ratio of 2:1.

[0011] As a preferred embodiment of the etching method for revealing the original austenite grain boundaries of martensitic steel according to the present invention, wherein: in step S2, the etching solution B is an aqueous solution, and each 100 mL of the etching solution B contains 2 - 5 g of potassium permanganate and 2 - 10 mL of concentrated sulfuric acid.

[0012] As a preferred embodiment of the etching method for revealing the original austenite grain boundaries of martensitic steel according to the present invention, wherein: in step S3, the cleaning solution is an aqueous solution, and each 100 mL of the cleaning solution contains 5 - 10 mL of oxalic acid.

[0013] The beneficial effects of the present invention are as follows:

[0014] The present invention provides an etching method for revealing the original austenite grain boundaries of martensitic steel. The etching solution of the present invention does not contain picric acid, nitric acid alcohol solution, and aqua regia, has low danger, is easy to obtain raw materials, the etching process is simple and efficient, and the original austenite grain boundaries of martensitic steel can be clearly revealed without using complex equipment for electrochemical etching; a mixed solution of hydrofluoric acid and hydrogen peroxide is selected as the etchant for the original austenite grain boundaries of martensitic steel. Because the corrosiveness of the etchant is exactly matched with the corrosion resistance of the grain boundaries of martensitic steel with medium and low carbon and Cr content ≤ 15 wt% (such as medium carbon Cr5 and Cr15), it is sensitive to the grain boundaries, can make the grain boundaries clearly shown, is insensitive to the martensite structure in the grains, has a good inhibitory effect, and cannot make it shown, thus obtaining a perfect display effect of austenite grain boundaries. Description of the Drawings

[0015] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for use in the description of the embodiments or the prior art. Obviously, the following drawings are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on the structures shown in these drawings.

[0016] Figure 1 It is a photograph showing the austenite grain boundaries of medium carbon Cr5 steel in Example 1.

[0017] Figure 2 It is a photograph showing the austenite grain boundaries of medium carbon Cr15 steel in Example 2.

[0018] Figure 3 Photograph showing the austenite grain boundaries of medium-carbon Cr5 steel in Example 3.

[0019] Figure 4 Photograph showing the austenite grain boundaries of medium-carbon Cr5 steel in Comparative Example 1.

[0020] Figure 5 Photograph showing the austenite grain boundaries of medium-carbon Cr5 steel in Comparative Example 2.

[0021] Figure 6 Photograph showing the austenite grain boundaries of medium-carbon Cr5 steel in Comparative Example 3.

[0022] The realization, functional features and advantages of the object of the present invention will be further described with reference to the embodiments and the accompanying drawings. Detailed Embodiments

[0023] The technical solutions in the embodiments will be clearly and completely described below. Apparently, the described embodiments are only a part of the embodiments of the present invention, rather than all of them. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the scope of protection of the present invention.

[0024] The present invention provides a corrosion method for displaying the original austenite grain boundaries of martensitic steel, which can clearly display the original austenite grain boundaries of medium-low carbon martensitic steel with a Cr content ≤ 15 wt% after actual heat treatment. By analyzing the grain boundaries, problems such as grain coarsening and mixed grain structure can be judged, providing an important basis for formulating the production process.

[0025] The erosiveness and corrosion resistance of hydrofluoric acid in Corrosion Solution A are matched and will not overly corrode the grain boundaries and damage the protective layer. Hydrogen peroxide is used to improve the reaction activity of the solution; and because Corrosion Solution A will react with the austenite grain boundaries first, but the grain boundary display in some finer areas or other areas that are not easily corroded will be unclear. At this time, using Corrosion Solution B can effectively display the grain boundaries in these areas that are not easily corroded. The corrosiveness of Corrosion Solution B is weaker than that of Corrosion Solution A and will not overly corrode the grain boundaries corroded by Corrosion Solution A. Then, cleaning with the cleaning solution can make the grain boundaries appear cleaner and more complete.

[0026] According to one aspect of the present invention, the present invention provides the following technical solution:

[0027] A corrosion method for displaying the original austenite grain boundaries of martensitic steel, comprising the following steps:

[0028] S1. Prepare a metallographic specimen of martensitic steel;

[0029] S2. Dip absorbent cotton in etching solution A and wipe the polished surface of the specimen forcefully until a silver-gray foggy surface appears. Then, immerse the polished surface of the specimen upward in etching solution B for thermal etching. After thermal etching, take out the specimen and rinse the residual etching solution on the surface of the specimen.

[0030] S3. Immerse the polished surface of the specimen to be tested after etching in the cleaning solution, then rinse and dry it to reveal the original austenite grain boundaries of the martensitic steel.

[0031] Preferably, in step S1, the martensitic steel is medium-carbon Cr5 steel or medium-carbon Cr15 steel. By mass percentage, medium-carbon Cr5 steel includes C: 0.48 - 0.6%; Si: 0.4 - 0.62%; Mn: 0.3 - 0.6%; P ≤ 0.035%; S ≤ 0.040%; Cr: 4.5 - 5.5%, and the balance is Fe and unavoidable impurities. By mass percentage, medium-carbon Cr15 steel includes C: 0.4 - 0.52%; Si: 0.3 - 0.8%; Mn: 0.25 - 0.55%; P ≤ 0.025%; S ≤ 0.025%; Cr: 14.5 - 15.5%, and the balance is Fe and unavoidable impurities.

[0032] Preferably, in step S1, grind and polish the surface to be detected of the martensitic steel specimen to obtain a polished surface, then clean and dry it to obtain a martensitic steel metallographic specimen.

[0033] Preferably, in step S2, etching solution A is a mixed solution of hydrofluoric acid and hydrogen peroxide with a volume ratio of 2:1.

[0034] More preferably, in step S2, the preparation method of etching solution A is as follows: Take hydrofluoric acid in a beaker, then measure and slowly add hydrogen peroxide with a volume of 1 / 2 of the volume of hydrofluoric acid into the beaker, and stir with a glass rod to make it mix evenly. Even more preferably, the concentration of hydrogen peroxide is 3 - 35 wt%, and the concentration of hydrofluoric acid is 5 - 49 wt%.

[0035] Preferably, in step S2, etching solution B is an aqueous solution, and each 100 mL of etching solution B contains 2 - 5 g of potassium permanganate and 2 - 10 mL of concentrated sulfuric acid.

[0036] More preferably, in step S2, the preparation method of etching solution B is as follows: Take a small amount of deionized water in a beaker, measure and slowly add 2 - 10 mL of concentrated sulfuric acid into the beaker, stir with a glass rod to make it mix evenly, then weigh 2 - 5 g of potassium permanganate and pour it into the beaker, continuously stir with a glass rod until the potassium permanganate is completely dissolved, and then add deionized water to mix and make up the volume to 100 mL. Even more preferably, the purity of potassium permanganate is ≥99%, and the concentration of concentrated sulfuric acid is 95 - 98 wt%.

[0037] Preferably, in the step S2, the thermal corrosion is carried out in a water bath, the temperature of the corrosion solution B is 60-70°C, and the thermal corrosion time is 2-4 min.

[0038] Preferably, in the step S3, the cleaning solution is an aqueous solution, and each 100 mL of the cleaning solution contains 5-10 mL of oxalic acid.

[0039] More preferably, in the step S3, the preparation method of the cleaning solution is: add 5-10 mL of oxalic acid to a small amount of deionized water in a beaker and mix evenly, then continue to add deionized water and mix and make up the volume to 100 mL. Even more preferably, the purity of the oxalic acid is ≥99%.

[0040] Preferably, in the step S3, the polished surface of the specimen to be tested after corrosion is soaked in the cleaning solution, and then rinsed with alcohol and dried.

[0041] The technical solution of the present invention will be further described below in conjunction with specific embodiments.

[0042] In the following embodiments, the concentration of hydrogen peroxide is 7.7 wt%; the concentration of hydrofluoric acid is 40 wt%; the purity of potassium permanganate is 99%; the concentration of concentrated sulfuric acid is 98%; the purity of oxalic acid is 99.5%.

[0043] Example 1

[0044] A corrosion method for showing the original austenite grain boundaries of martensitic steel, comprising the following steps:

[0045] S1. Prepare a martensitic steel metallographic specimen; the martensitic steel is medium-carbon Cr5 steel, which, by mass percentage, includes C: 0.53%; Si: 0.51%; Mn: 0.52%; P: 0.006%; S: 0.003%; Cr: 5.07%, and the balance is Fe and unavoidable impurities; this medium-carbon Cr5 steel metallographic specimen is taken from a large forging and obtained through post-forging normalizing, spheroidizing annealing and tempering treatments. The surface to be detected of the specimen is ground and polished to obtain a polished surface, and then cleaned and dried with alcohol;

[0046] S2. Dip a piece of absorbent cotton in the corrosion solution A (a mixed solution of 10 mL of hydrofluoric acid and 5 mL of hydrogen peroxide), wipe the polished surface of the specimen forcefully until a silver-gray foggy surface appears, and then immerse the polished surface of the specimen upward in the corrosion solution B (the corrosion solution B is an aqueous solution, and each 100 mL of the corrosion solution B contains 2 g of potassium permanganate and 5 mL of concentrated sulfuric acid) for thermal corrosion. The thermal corrosion is carried out in a water bath, the temperature of the corrosion solution B is 65°C, and the thermal corrosion time is 2.5 min. After the thermal corrosion, take out the specimen and rinse the residual corrosion solution on the surface of the specimen;

[0047] S3. Immerse the polished surface of the specimen to be tested after etching in a cleaning solution (the cleaning solution is an aqueous solution, and each 100 mL of the cleaning solution contains 8 mL of oxalic acid), then rinse with alcohol and dry to reveal the austenite grain boundaries of the martensitic steel; observe its austenite grain boundaries under a metallographic microscope, as shown in Figure 1 .

[0048] Example 2

[0049] A corrosion method for revealing the prior austenite grain boundaries of martensitic steel, comprising the following steps:

[0050] S1. Prepare a metallographic specimen of martensitic steel; the martensitic steel is medium-carbon Cr15 steel, which, by mass percentage, includes C: 0.48%; Si: 0.50%; Mn: 0.45%; P: 0.006%; S: 0.002%; Cr: 15.12%, and the balance is Fe and inevitable impurities; this medium-carbon Cr15 steel metallographic specimen is obtained by quenching the as-cast medium-carbon Cr15 steel after hot compression. Grind and polish the surface of the specimen to be tested to obtain a polished surface, then clean and dry it with alcohol;

[0051] S2. Dip absorbent cotton in corrosion solution A (a mixed solution of 10 mL of hydrofluoric acid and 5 mL of hydrogen peroxide), wipe the polished surface of the specimen forcefully until a silver-gray foggy surface appears, then immerse the polished surface of the specimen upward in corrosion solution B (the corrosion solution B is an aqueous solution, and each 100 mL of the corrosion solution B contains 2 g of potassium permanganate and 5 mL of concentrated sulfuric acid) for thermal corrosion. The thermal corrosion is carried out in a water bath, the temperature of the corrosion solution B is 65 °C, the thermal corrosion time is 4 min, take out the specimen after thermal corrosion, and rinse the residual corrosion solution on the surface of the specimen;

[0052] S3. Immerse the polished surface of the specimen to be tested after etching in a cleaning solution (the cleaning solution is an aqueous solution, and each 100 mL of the cleaning solution contains 8 mL of oxalic acid), then rinse with alcohol and dry to reveal the prior austenite grain boundaries of the martensitic steel; observe its austenite grain boundaries under a metallographic microscope, as shown in Figure 2 .

[0053] Example 3

[0054] A corrosion method for revealing the prior austenite grain boundaries of martensitic steel, comprising the following steps:

[0055] S1. Prepare a metallographic specimen of martensitic steel; the martensitic steel is medium-carbon Cr5 steel, which, by mass percentage, includes C: 0.5%; Si: 0.5%; Mn: 0.52%; P: 0.008%; S: 0.005%; Cr: 5.03%, and the balance is Fe and unavoidable impurities; this medium-carbon Cr5 steel metallographic specimen is taken from a large forging and obtained through normalizing after forging, spheroidizing annealing, quenching, and tempering. Grind and polish the surface of the specimen to be tested to obtain a polished surface, clean it with alcohol, and dry it.

[0056] S2. Dip a piece of absorbent cotton in etching solution A (a mixed solution of 10 mL of hydrofluoric acid and 5 mL of hydrogen peroxide), and wipe the polished surface of the specimen forcefully until a silver-gray foggy surface appears. Then, immerse the polished surface of the specimen upward in etching solution B (etching solution B is an aqueous solution, and each 100 mL of etching solution B contains 3 g of potassium permanganate and 6 mL of concentrated sulfuric acid) for thermal etching. The thermal etching is carried out in a water bath, the temperature of etching solution B is 70 °C, the thermal etching time is 3 min. After thermal etching, take out the specimen and rinse the residual etching solution on the surface of the specimen.

[0057] S3. Immerse the polished surface of the specimen to be tested after etching in a cleaning solution (the cleaning solution is an aqueous solution, and each 100 mL of cleaning solution contains 10 mL of oxalic acid), then rinse it with alcohol and dry it to display the original austenite grain boundaries of the martensitic steel; observe its austenite grain boundaries under a metallographic microscope, and see Figure 3 .

[0058] Comparative Example 1

[0059] The difference from Example 1 is that the component ratio of the etching solution is: nitric acid with a mass fraction of 65%: alcohol = 2 mL: 98 mL. According to the above component ratio of the etching solution, add nitric acid and alcohol to the container in sequence and stir evenly; place the polished surface of the specimen upward into the prepared etching solution; take out the specimen after etching at room temperature for 8 min; rinse the residual etchant on the surface with alcohol, and then dry it.

[0060] Observe its austenite grain boundaries under a metallographic microscope, and see Figure 4 .

[0061] Comparative Example 2

[0062] The difference from Example 1 is that in step S2, an etching solution (component ratio: hydrochloric acid with a mass fraction of 35%: alcohol = 10 mL: 90 mL) is used to replace etching solution A and etching solution B in Example 1.

[0063] Observe its austenite grain boundaries under a metallographic microscope, and see Figure 5 .

[0064] Comparative Example 3

[0065] The difference from Example 1 is that in step S2, the polished surface of the wiping specimen is not wiped with etching solution A, and the polished surface of the specimen is directly immersed face up in etching solution B (etching solution B is an aqueous solution, and each 100 mL of etching solution B contains 2 g of potassium permanganate and 5 mL of concentrated sulfuric acid) for thermal etching. The thermal etching is carried out in a water bath. The temperature of etching solution B is 65 °C, and the thermal etching time is 2.5 min. After thermal etching, the specimen is taken out and the residual etching solution on the surface of the specimen is rinsed.

[0066] Observe its austenite grain boundaries under a metallographic microscope, and see Figure 6 .

[0067] Compare Figures 1 to 6 It can be found that the austenite grain boundaries obtained in Examples 1-3 of the present invention are respectively as Figures 1 - 3 shown, Figure 1 In the Cr5 steel in Figure 2 , the grain shape and size can be seen relatively clearly, and the grain boundary contour between grains is also relatively obvious; Figure 3 In the Cr15 steel in Figure 1 , the grain boundaries and grain shapes between grains can be seen very clearly, and relatively small grains can also be shown; Figure 3 The Cr5 steel in Figure 4 and the Cr5 steel in Figure 5 are materials with similar Cr contents, Figure 6 In

[0068] The present invention can simply and clearly etch the original austenite grain boundaries of martensitic steel, and the present invention can etch multiple specimens at one time, with simple operation; the grain boundaries etched by the present invention are clear, and the grain size of the steel can be evaluated by the comparison method or the intercept method, providing a basis for formulating a reasonable production system for such steel types, thereby effectively controlling the grain size and obtaining excellent structures and properties. By etching specimens in different states, the grain grade can also be evaluated.

[0069] The above are only the preferred embodiments of the present invention, and do not limit the patent scope of the present invention accordingly. Any equivalent structural transformation made using the content of the specification of the present invention under the inventive concept of the present invention, or direct / indirect application in other related technical fields, is included in the patent protection scope of the present invention.

Claims

1. A corrosion method for revealing the prior austenite grain boundaries of martensitic steel, characterized in that, It includes the following steps: S1. Prepare a martensitic steel metallographic specimen; S2. Dip absorbent cotton in etching solution A and wipe the polished surface of the specimen forcefully until a silver-gray foggy surface appears. Then immerse the polished surface of the specimen upward in etching solution B for thermal etching. After thermal etching, take out the specimen and rinse the residual etching solution on the surface of the specimen; S3. Immerse the polished surface of the specimen to be tested after etching in the cleaning solution, then rinse and dry it to display the original austenite grain boundaries of the martensitic steel.

2. The etching method for revealing prior austenite grain boundaries of martensitic steel according to claim 1, characterized in that, In the step S1, the martensitic steel is medium-carbon Cr5 steel and medium-carbon Cr15 steel.

3. The etching method for revealing prior austenite grain boundaries of martensitic steel according to claim 1, characterized in that, In the step S2, the etching solution A is a mixed solution of hydrofluoric acid and hydrogen peroxide with a volume ratio of 2:

1.

4. The etching method for revealing prior austenite grain boundaries of martensitic steel according to claim 3, wherein, In the step S2, the concentration of hydrogen peroxide is 3-35 wt%, and the concentration of hydrofluoric acid is 5-49 wt%.

5. The etching method for revealing prior austenite grain boundaries of martensitic steel according to claim 1, characterized in that, In the step S2, the etching solution B is an aqueous solution, and each 100 mL of the etching solution B contains 2-5 g of potassium permanganate and 2-10 mL of concentrated sulfuric acid.

6. The etching method for revealing prior austenite grain boundaries of martensitic steel according to claim 5, characterized in that, In the step S2, the purity of potassium permanganate is ≥99%, and the concentration of concentrated sulfuric acid is 95-98 wt%.

7. The etching method for revealing prior austenite grain boundaries of martensitic steel according to claim 1, characterized in that, In the step S2, the thermal etching is carried out in a water bath. The temperature of the etching solution B is 60-70 °C, and the thermal etching time is 2-4 min.

8. The etching method for revealing prior austenite grain boundaries of martensitic steel according to claim 1, characterized in that, In the step S3, the cleaning solution is an aqueous solution, and each 100 mL of the cleaning solution contains 5-10 mL of oxalic acid.

9. The etching method for revealing prior austenite grain boundaries of martensitic steel according to claim 8, wherein, In the step S3, the purity of oxalic acid is ≥99%.

Citation Information

Patent Citations

  • Corrosive liquid displaying ultrahigh-strength steel austenite grain boundary and martensite, preparation method and application

    CN110468416A

  • Precipitation-strengthened martensitic stainless steel original austenite grain boundary corrosion method

    CN111638113A

  • Corrosive agent for inspecting 16MnCr5 steel austenite grain boundary and inspection method thereof

    CN113358646A